Selecting a Suitable Synthesis of Industrial Hot Melt Nanostructured Polyurethane Adhesives for the Enhanced Bonding of MDF and PVC Veneers - A Review - Khorshidi, Fatemeh Hassani; Saadatabadi, Ahmad Ramazani; Pizzi, Antonio; Fatriasari, Widya (Jurnal Sylva Lestari, 2025)
This review focuses on the synthesis and application of industrial hot-melt nanostructured polyurethane adhesives (HMPUAs) used for enhancing the bonding of medium-density fiberboard (MDF) with polyvinyl chloride (PVC) veneers. The use of PVC veneers has been identified as an effective approach to protect wood composite products, particularly MDF, due to its resistance to moisture, environmental conditions, and cost-effectiveness. However, achieving strong adhesion between PVC and MDF remains challenging due to differences in their chemical and structural properties. This study compares various synthesis methods of polyurethane adhesives, emphasizing the prepolymer method as the most efficient approach for producing high-performance HMPUAs. Key challenges include optimizing the isocyanate to hydroxyl group ratio (NCO/OH), selecting appropriate polyols, and incorporating suitable additives. The effects of nanoparticles, including nanosilica, nanolignin, phosphorus, nitrogen compounds, mica particles, and aluminum trihydrate, on the mechanical and thermal properties of polyurethane adhesives are thoroughly discussed. Furthermore, the challenges of achieving consistent adhesive performance, compatibility, and durability under varying environmental conditions are addressed. The findings of this review provide essential insights into improving the synthesis of one-component HMPUAs and enhancing their applicability in MDF-PVC veneer bonding. Keywords: additives, hot melt adhesive, medium-density fiberboard, polyurethane, reactive resin